A Comprehensive Algebraic Framework for Fuzzy Graphs and Their Operators - Aburub, Faisal Asad Farid; N, Yogeesh; Mohammad, Suleiman Ibrahim Shelash; Raja, N; Lingaraju, Lingaraju; William, P.; Vasudevan, Asokan; Hunitie, Mohammad Faleh Ahmmad (Journal of Posthumanism, 2024)
This study presents a comprehensive algebraic framework for fuzzy graphs that extends classical graph theory to accommodate uncertainty and partial relationships. We define fuzzy graph operators namely, fuzzy union (via the maximum function), fuzzy intersection (via the minimum function), and fuzzy complement (via membership inversion) and demonstrate that these operations endow the set of fuzzy graphs with an idempotent semiring or lattice-like structure. Fundamental graph-theoretic concepts such as homomorphisms, isomorphisms, and structural invariants (including degree sequences and connectivity measures) are rigorously redefined within this fuzzy context, with detailed proofs and illustrative examples provided. Through step-by-step computations and visualizations using this concept, we highlight how our approach not only recovers classical crisp graph properties as a special case but also offers enhanced analytical capabilities for modeling real-world networks characterized by uncertainty. Additionally, potential extensions to intuitionistic fuzzy graphs, interval-valued fuzzy graphs, and multi-attribute fuzzy structures are discussed, along with computational implications and applications in network analysis and decision support systems. This framework's consistency and completeness were validated through rigorous proofs, ensuring that all fuzzy operations remain coherent with their classical counterparts. Moreover, the framework facilitates efficient algorithm design and opens new research directions, thereby providing a unified platform for both theoretical advancements and practical applications in complex network analysis.